Polite vocabulary in the Javanese language of Surabaya - Krauße, Daniel (Wacana, Journal of the Humanities of Indonesia, 2018)
Surabaya and its surroundings are known for their peculiar dialect, which does not only exhibit very characteristic phonological and morphological features, but also has a politeness, honorific, and deferential system that has so far remained largely understudied. It is the aim of this paper to shed further light on the sociolinguistic situation of the Javanese dialect of the city of Surabaya, East Java, Indonesia with a focus on the polite vocabulary (Krama, Krama Andhap, and Krama Inggil). Although to the Central Javanese ear, speakers of Surabayan Javanese sound discourteous, they by no means are impolite. After a general introduction about the linguistic situation in Surabaya, a brief typological summary of politeness systems throughout the world is given, which helps debunk the persistent language myth that speakers of Surabayan Javanese are rude. This paper will show that the dialect rather exhibits a binary T-V distinction in politeness similar to that in French and German, as opposed to the strict speech level system as found in Central Javanese, Korean, and Japanese.